Impact of Project Size and Social Cost Benefit Analysis on Capital Budgeting Decisions of Indian Firms - Gupta, Divya (Indian Journal of Finance, 2013)
Purpose: This paper is an exploratory research on the application of capital budgeting techniques in Indian companies. Two parameters - project size and social cost benefit analysis were considered for the study and the influence of these factors for the adoption of capital budgeting techniques by the Indian companies has been analyzed. Design/Methodology: This paper is based on the primary data. OLS (observed least square model) was used to evaluate the degree of relationship between project size and social cost benefit analysis with the frequency of usage of capital budgeting techniques in the companies and with the type of capital budgeting techniques used by the companies. Findings: Using a sample size of 75 companies, the result shows that there is a positive relationship between frequency of usage of capital budgeting techniques and application of discounted cash flow techniques with the firm project size and social cost benefit analysis. Practical Implications: The paper provides information to the students and researchers about the practices adopted in the Indian companies related to capital budgeting techniques. Originality/Value: The paper provides new insights about the frequency of the capital budgeting techniques used in the firms along with the type of technique used by the companies.